Application of Structural Batteries in EV Quadricycles Life cycle assessment and design strategies for sustainable integration in vehicles - Gustavsson, William; Persson, Isak (My University, 2025)
This thesis investigates the integration of structural battery composites (SBCs) in lightweight electric vehicles with a focus on the EU L6e-class quadricycle category. SBCs are multifunctional materials that combine load-bearing and energy storage capabilities offering the potential to significantly reduce vehicle weight, improve energy efficiency, and lower life cycle emissions. The aim of this research is to provide theoretical technical design guidance for application of future SBC technology in lightweight electric vehicles. This was investigated through a literature review covering the emerging field of structural battery composites, lightweight electric vehicles (particularly quadricycles) and eco-design principles. A weight reduction analysis was conducted to assess the potential of SBC integration in specific vehicle components and to inform future design strategies. A screening life cycle assessment was used to investigate the potential environmental implications when integrating SBCs and to analyze potential greenhouse gas emission reductions. The findings show that SBC integration has the potential to significantly reduce component and vehicle weight, while also improving vehicle efficiency. If future production emissions are reduced, SBCs could also lower the overall life cycle emissions of electric vehicles.
Keywords: L6e Quadricycle; Structural Battery Composite (SBC); Lightweight EV; Eco-Design; Multifunctional materials; Weight reduction; Sustainable vehicle technology; Lightweighting